Algumas reflexões sobre a classificação de orações gerundivas em Português Europeu - Silvano, Maria da Purificação (2019)
This paper addresses different problems related to gerund clauses in European Portuguese. In the first part, we analyze from a semantic point of view examples of gerund clauses with compound gerund that occur after the main clause, taking into account parameters such as the rhetorical and temporal relations that are established between the situations denoted by the gerund clauses and the main clauses. The analysis of the data allows us to question the distinction between sentence gerund clauses and coordinate gerund clauses that is proposed in the literature. In the second part of the article, a preliminary analysis of gerund clauses introduced by como with both compound and simple gerund is made, and it is shown that these constructions have peculiarities that make them difficult to catalog within the prevailing typologies.